2012
DOI: 10.1039/c2jm34479c
|View full text |Cite
|
Sign up to set email alerts
|

Antisite defects in Ce-doped YAG (Y3Al5O12): first-principles study on structures and 4f–5d transitions

Abstract: The interactions between Ce 3+ and antisite defects (AD) in YAG (Y 3 Al 5 O 12 ) are studied by means of first-principles calculations: Periodic-boundary-conditions density-functional-theory for a 160 atom YAG unit cell with one Ce 3+ and one or two ADs, and complete-active-space secondorder perturbation theory for the 4f 1 , 5d 1 , and 6s 1 electronic manifolds of the (CeO 8 Al 2 O 4 ) 15− embedded cluster. Attractive interactions are found between Ce 3+ and the ADs. The formation of one AD is more favorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 54 publications
0
21
0
2
Order By: Relevance
“…George et al 22 studied the local environment of Ce 3+ activators in Y 3 Al 5 O 12 :Ce phosphors and found that the random distribution of Ce 3+ ions in YAG lattice could result in the slight expansion of YAG unit cell, which played critical roles in enhancing quantum yield and preventing from photoluminescence quenching. Belén et al 23 studied the interplay between the Ce Y and Y Al -Al Y in YAG by using the first-principles calculations and found that the presence of Y Al -Al Y could cause a strongly anisotropic expansion of the atomistic structure around the Ce Y impurities and decrease the effective ligand-field splitting of the 5 d 1 manifold, leading to the blue-shifts the two lowest Ce 3+ 4f–5d transitions. Although the photoluminescence properties of Ce 3+ ions in garnet structure were investigated24, the detailed relationship between the photoluminescence properties and the local structures as well as the distributions of activators in Ce 3+ -doped YAG phosphors have been rarely studied experimentally.…”
mentioning
confidence: 99%
“…George et al 22 studied the local environment of Ce 3+ activators in Y 3 Al 5 O 12 :Ce phosphors and found that the random distribution of Ce 3+ ions in YAG lattice could result in the slight expansion of YAG unit cell, which played critical roles in enhancing quantum yield and preventing from photoluminescence quenching. Belén et al 23 studied the interplay between the Ce Y and Y Al -Al Y in YAG by using the first-principles calculations and found that the presence of Y Al -Al Y could cause a strongly anisotropic expansion of the atomistic structure around the Ce Y impurities and decrease the effective ligand-field splitting of the 5 d 1 manifold, leading to the blue-shifts the two lowest Ce 3+ 4f–5d transitions. Although the photoluminescence properties of Ce 3+ ions in garnet structure were investigated24, the detailed relationship between the photoluminescence properties and the local structures as well as the distributions of activators in Ce 3+ -doped YAG phosphors have been rarely studied experimentally.…”
mentioning
confidence: 99%
“…The data on ceramics seem to contradict the first principle calculation [37] of Ce 3+ -antisite defects interaction in Ce:YAG that predict shifts of 5d 1 level only toward large energy, that is unlikely if the analyzed results on RE 3+ are considered; experimentally it is difficult to separate those at higher energies due to broad bands absorption. One must mention also that the modeling in Ref.…”
Section: 2mentioning
confidence: 56%
“…One must mention also that the modeling in Ref. [37] is based on the assumption of large Y 3+ M Al 3+ inversion proposed in Ref. [33], a supposition not proved experimentally.…”
Section: 2mentioning
confidence: 96%
“…Since the presence of such defects is inevitable, the investigations of their nature and specifically their relation to the materials' optical properties have become increasingly important. Examples of recent works in this context include studies by Stanek et al [77] and Muñoz-García et al [78], who have predicted different defect structures in garnet phosphors and the effects of antisite defects on the electronic configurations of Ce 3? for YAG:Ce 3?…”
Section: F-5d Transitions In Yag:ce 31mentioning
confidence: 99%